ASSESSMENT OF AMNIOTIC FLUID INDEX IN NORMAL PREGNANCY AT A TERTIARY CARE HOSPITAL SETTING - Ali, Habiba Sharaf (Journal of Ayub Medical College Abbottabad, 2009)
Background: Ultrasound assessment of amniotic fluid has important implication in obstetrics care and it has become an integral and important component of pregnancy assessment. Changes in amniotic fluid volume are associated with adverse outcome. Excess volume is associated with foetal anomalies and aneuploidy and less volume is associated with Intra Uterine Growth Retardation, renal anomalies in the second trimester. The objective of this study was to establish a normative scale of Amniotic Fluid Index (AFI) throughout gestation in uncomplicated singleton pregnancies, and to identify the lower and upper limits for each gestational week. Method: A prospective cross-sectional study conducted in a private tertiary care Hospital from Jan 2004 to April 2005. Amniotic fluid index was calculated in 400 women attending the antenatal clinic. The gestational age of these women range from 20-40 weeks. Women with foetal anomalies, Pregnancy Induced Hypertension, Diabetes Mellitus and other maternal complication were excluded from study. The median, mean, 5th, 50th, and 95th percentile were calculated for each gestation and these values are compared with other studies. Results: The amniotic fluid index observations from regression equation curve were stratified in week-specific normative curves. The mean of preterm was significantly greater than mean of term gestation (p<0.05). Our median reached peak at 27th week of gestation another peak at 30-31 week. The values then begin a gradual fall to 40 weeks gestation. Conclusion Gestational age specific values of AFI were established, showing significant trends of changes in the amniotic fluid volume with gestation. Keywords: Amniotic fluid index, normal pregnancy, Pakistan